Heroes and victims : remembering war in twentieth-century Romania - Bucur, Maria, 1968- (Indiana-Michigan series in Russian and East European studies., 2010)
Heroes and victims explores the cultural power of war memorials in 20th-century Romania through two world wars and a succession of radical political changes -- from attempts to create pluralist democratic political institutions after World War I to shifts toward authoritarian rule in the 1930s, to military dictatorships and Nazi occupation, to communist dictatorships, and finally to pluralist democracies with populist tendencies. Examining the interplay of centrally articulated and locally developed comme.